2016
DOI: 10.1038/ajg.2015.390
|View full text |Cite
|
Sign up to set email alerts
|

In the Intestinal Mucosa of Children With Potential Celiac Disease IL-21 and IL-17A are Less Expressed than in the Active Disease

Abstract: CONCLUSIONS:In potential CD, IL-21 is less expressed than in active CD; however, IL-21-producing cells are present and prone to respond after specifi c stimuli. This suggests a key role of IL-21 in the progression of mucosal damage in CD.SUPPLEMENTARY MATERIAL is linked to the online version of the paper at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Although a reduced mucosal infiltration of IL21‐positive cells in potential‐CD has been reported, we have previously demonstrated that in the gut mucosa of this peculiar group of CD patients, IL‐21‐producing cells are present and prone to respond after strong stimuli, as the PMA/ion mitogen or gliadin in organ culture. These results, obtained in a different cohort of children with potential‐CD, confirm and corroborate our previous findings . Interestingly, the potential‐ and overt‐CD were characterized by two distinct subsets of Th1 cells.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although a reduced mucosal infiltration of IL21‐positive cells in potential‐CD has been reported, we have previously demonstrated that in the gut mucosa of this peculiar group of CD patients, IL‐21‐producing cells are present and prone to respond after strong stimuli, as the PMA/ion mitogen or gliadin in organ culture. These results, obtained in a different cohort of children with potential‐CD, confirm and corroborate our previous findings . Interestingly, the potential‐ and overt‐CD were characterized by two distinct subsets of Th1 cells.…”
Section: Discussionsupporting
confidence: 91%
“…IL21 is a key mediator in the pathogenesis of villous atrophy as demonstrated by several studies in both adult and childhood CD . In particular, CD4 + T cells releasing IL21 were found increased in inflamed mucosa of overt‐CD patients and able to stimulate the tissue production of IFN‐γ and T‐bet (Th1 transcription factor) .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, many such individuals are asymptomatic and do not develop duodenal lesions even during a long-term follow-up [49, 105107]. It is essential to learn more about the natural history of early developing celiac disease in order to discern cases that would truly benefit from early diagnosis [108].…”
Section: Challenges With the Diagnostic Criteria And Future Directmentioning
confidence: 99%